FOREIGN EXPERIENCE OF ENERGY-EFFICIENT GREEN CONSTRUCTION - Bondarchuk, Maryna; Martynov, Viacheslav (Theory and practice of design, 2023)
A study of the global experience of designing energy-efficient green buildings was conducted. The issue of development of design and construction of energy-efficient green residential buildings is under consideration. Purpose. To investigate and substantiate the trends in the development of energy-efficient green construction. Outline the main characteristics of energy-efficient construction. To study the foreign experience of energy-efficient construction. To outline volume-planning and structural solutions typical for energy-efficient construction. Conduct a comparative analysis of methods, techniques and technologies, as well as building materials used in the construction of energy-efficient buildings. Methodology. The analysis of literary sources and foreign experience is used as research methods to justify the results. Results. The research results showed the main principles and practices of energy- efficient green construction: minimization of energy consumption; environmental design; effective insulation and construction; efficient heating and air conditioning system; use of renewable energy sources; water conservation; materials with minimal impact; waste management; health and comfort. A comparative analysis of methods, techniques and technologies, as well as building materials used in the construction of energy-efficient buildings, was conducted. The scientific novelty of this research lies in the comprehensive analysis and formation of energy-efficient green buildings, as well as their impact on the environment. The study covers not only architectural components, but also innovative methods of using interactive technologies. Practical relevance. Understanding the basic principles of energy-efficient construction will help in the fight against climate change and environmental pollution, since the construction and operation of buildings is one of the main causes of energy consumption and greenhouse gas emissions.